The Concept of Rwa Bhineda Kriya on the Island of Bali towards Jagadhita - I Ketut Sunarya (Wacana Seni Journal of Arts Discourse, 2020)
The concept of “rwa bhineda” on the island of Bali is reflected in the intertwining of “kriya,” religion, tourism and local customs as regulators. These qualities make “kriya” beautiful because it is very adequate in carrying out its functions, namely meeting religious and non-religious needs. This art is sacred and profane, reflecting the nature of “kaja” (north) and “kelod” (south), which denotes mountains and sea, or upstream (above) and “teben” (below). In “kriya” on the island of Bali, this concept is manifested in the form of “barong” and “rangda” as symbols of good and evil. The “kriya,” which appear creepy, frightening, but making you miss it, have a function as decorations, making the temple beautiful and comfortable like heaven on earth. This situation shows the activities of the Balinese Hindu community at the ceremonial level and also tourism is full of “kriya” dynamics. This art grows and develops in various variations, emerging as a continuous manifestation of the soul in fulfilling the necessities of life towards the “jagadhita.”